High sensitive and large dynamic range quasi-distributed sensing system based on slow-light π-phase-shifted fiber Bragg gratings - Dwivedi, K.M.; Osuch, T.; Trivedi, G. (Opto-Electronics Review, 2019)
n this paper, we theoretically analyze the slow-light π-phase-shifted fiber Bragg grating (π-FBG) and its applications for single and multipoint/quasi-distributed sensing. Coupled-mode theory (CMT) and transfer matrix method (TMM) are used to establish the numerical modeling of slow-light π-FBG. The impact of slow-light FBG parameters, such as grating length (L), index change (Δn), and loss coefficient (α) on the spectral properties of π-FBG along with strain and thermal sensitivities are presented. Simulation results show that for the optimum grating parameters L = 50 mm, Δn = 1.5×10−4, and α = 0.10 m-1, the proposed slow-light π-FBG is characterized with a peak transmissivity of 0.424, the maximum delay of 31.95 ns, strain sensitivity of 8.380 με-1, and temperature sensitivity of 91.064 °C-1. The strain and temperature sensitivity of proposed slow-light π-FBG is the highest as compared to the slow-light sensitivity of apodized FBGs reported in the literature. The proposed grating have the overall full-width at half maximum (FWHM) of 0.2245 nm, and the FWHM of the Bragg wavelength peak transmissivity is of 0.0798 pm. The optimized slow-light π-FBG is used for quasi-distributed sensing applications. For the five-stage strain quasi-distributed sensing network, a high strain dynamic range of value 1469 με is obtained for sensors wavelength spacing as small as 2 nm. In the case of temperature of quasi-distributed sensing network, the obtained dynamic range is of 133°C. For measurement system with a sufficiently wide spectral range, the π-FBGs wavelength grid can be broadened which results in substantial increase of dynamic range of the system.